Fetishism and panic disorder-an uneasy coexistence - Tze, Nicholas Ping Pang; Mohd Kassim, Mohd Amiruddin; Sze, Chet Lee; Chun, Keat Ng; Poh, Khuen Lim; Alimuddin, Aishah Siddiqah (ASEAN Federation of Psychiatry and Mental Health, 2023)
Fetishism is a distressing condition that may have a link with panic disorder. We highlight a 29-yearold man who presented with a constant urge to search for lace pillows to achieve his sexual satisfaction. He further reinforced his sexual behaviors with trips to hotels or acquaintances' houses, which ended with masturbatory acts. He did not have an erection problem and can achieve orgasm via common sexual acts. He also presented concurrently with symptoms of panic disorder. There was no family history of mental illness and he denied a history of childhood or sexual trauma. He was given psychoeducation on his condition and coping with the distress associated with his sexual acts. He was scheduled for intensive psychotherapy to instill insight and deal with his sexual difficulties. In conclusion, an assessment of the organic and psychological components of paraphilia should be undertaken to allow suitable and timely treatment if reversible.